Spontaneous polarization induced electrostatic charge in washable electret composite fabrics for reusable air-filtering application. (5th January 2022) - Ding, Sheng; Cao, Yihong; Huang, Fengting; Wang, Yuanfeng; Li, Jianna; Chen, Shiguo
Abstract: The performance of disposable face masks in blocking pathogenic microbes mainly relies on the ability of melt-blown fabrics to electrostatically adsorb air droplets. While their easy invalidity in electrostatic effect highly limits their use recyclability, leading to a heavy burden on the surrounding environment due to their decomposing difficulty. Thus, it is urgent to develop reusable air filtration fabrics. In this work, we report a washable electret air-filtering fabrics with negligible cytotoxicity by combining spontaneous polarizing photochromic molecule with electrospinning electret technology. The electrostatic charge and filtration efficiency of the composite fabrics were highly improved compared to the commercial polypropylene melt-blown fabrics. Moreover, due to its electrostatic charge induced by self-polarization, the photochromic Spiropyran(SP)/polystyrene(PS) electret fabrics can maintain high filtration performance (over 95%) towards PM0.3 particles and low air flow resistance (<343.2 Pa) even after 5 times of washing (by 75% ethanol)/drying cycles. The combination of self-polarization photochromic molecule and electret material with negligible toxicity would create high-performance reusable air filtering fabrics, thereby SP/PS composite fabrics have a potential application in eco-friendly recyclable air purification and isolation and protection of pathogenic microbes. Graphical abstract: Image 1 Highlights: Spontaneous polarization of arrayed spiropyran induces electrostatic charges. Enhanced surface charge density increases filtration efficiency of the composite fabrics. Filtration efficiency remains over 95% after 5 cycles of ethanol washing/drying. Airflow resistance also keeps lower than 343.2 Pa during the 5 cycles. The composite fabrics exhibit good biocompatibility.